ANALISIS USAHA DAN STRATEGI PENGEMBANGAN USAHA KECIL MENENGAH (UKM) GETHUK TAKE, TAWANGMANGU KARANGANYAR - Tisa Nur Khasanah; Sri Marwanti; Aulia Qonita (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2022)
The research aims to determine the amount of costs, revenues, profits, and business efficiency, determine the conditions of internal factors and external factors, develop alternative development strategies, and determine strategic priorities that are suitable for developing UKM Gethuk Take. The basic method of research is descriptive analytical method. The method of determining the location is purposive. Determination of key informants is done puposive. The analysis method used is (1) analysis of costs, revenues, profits, business efficiency (2) IFE and EFE matrices (3) IE and SWOT matrices (4) QSP matrix. The results showed that the total costs incurred by UKM Gethuk Take in December 2020 IDR 146,528,402.78 with fixed costs IDR 4,127,902.78 and variable costs IDR 142,400,500. Receipts IDR 176,622,00. Profit IDR 30,093,597.22. Business efficiency is 1.26 meaning UKM Gethuk Take is already efficient in running its business. The main internal factors that influence business conditions are that the capital is carried out independently (strengths) and the management of marketing management is less than optimal (weaknesses). The main external factor affecting business conditions is the proximity to tourist attractions (opportunities) and the Covid-19 outbreak has reduced people's purchasing power and limited tourism activities (threats). There are 14 alternative strategies generated from the SWOT matrix. The strategic priority for the development of Gethuk Take is to maximize the use of all digital marketing by taking advantage of developments in information and communication technology.